2012
DOI: 10.1111/j.1468-2958.2012.01427.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation in Response to Entertainment Portrayals of Moral Virtue

Abstract: Media psychologists have long puzzled over how individuals can experience enjoyment from entertainment such as tragedies that often elicit profound feelings of sadness. The present research examines the idea that a focus on ''meaningful'' entertainment and affective responses identified as ''elevation'' may provide a framework for understanding many examples of sad or dramatic entertainment. The results of this study suggest that many types of meaningful cinematic entertainment feature portrayals of moral virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
324
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 216 publications
(346 citation statements)
references
References 21 publications
21
324
1
Order By: Relevance
“…Initial evidence from forced-exposure experiments shows that challenging media can produce personal growth (Khoo, 2016;Oliver, Hartmann, & Woolley, 2012;Prestin, 2013). Future research should test not only selective exposure and immediate responses to recreational and challenging media, but also the long-term effects of selective media repertoires on personal growth and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Initial evidence from forced-exposure experiments shows that challenging media can produce personal growth (Khoo, 2016;Oliver, Hartmann, & Woolley, 2012;Prestin, 2013). Future research should test not only selective exposure and immediate responses to recreational and challenging media, but also the long-term effects of selective media repertoires on personal growth and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Our focus on insight is driven by the recognition that "meaningful" entertainment appears to frequently consist of stories that highlight fundamental values (e.g., compassion) or depictions of the human condition (e.g., mortality; Oliver, Hartmann, & Woolley, 2012). As such, meaningful entertainment provides the opportunity to reflect on important "lessons" such as the value of virtue, the beauty of compassion, or the resiliency of the human spirit.…”
Section: Gratifications Associated With Game Playmentioning
confidence: 99%
“…Items were drawn from a variety of sources with the intention of including items that would represent a range of responses including meaningful, positive, and negative affect (Algoe & Haidt, 2009;Edell & Burke, 1987;Oliver, 2008;Oliver et al, 2012;Oliver & Raney, 2011;Schnall, Roper, & Fessler, 2012). …”
mentioning
confidence: 99%
“…It is possible that the fulfilment of relatedness needs may be necessary for meaningful experiences, as well. Furthermore, recent research has demonstrated that mediainduced feelings of elevation (a type of meaningful affective response, see Oliver et al 2012a) after viewing portrayals of moral goodness are associated with experiences of connection to humanity (Oliver et al 2012b). …”
Section: Meaningfulness and Video Gamesmentioning
confidence: 99%
“…More specifically, media texts that explore difficult life questions tend to evoke meaningful responses, while media texts that are more light-hearted tend to lead to enjoyment (Oliver et al 2012a). Oliver and Hartmann's (2010) qualitative analysis of viewer descriptions of film experiences demonstrated that viewers described meaningful films as those that contemplate fundamental moral values, life lessons and difficult questions of human existence.…”
Section: Meaningful Entertainmentmentioning
confidence: 99%